RESOURCES REQUIRED IN CLINICAL PATHWAY FOR TYPHOID FEVER TREATMENT AT KALIWATES GENERAL HOSPITAL IN 2017 - Pratiti Swesti Komala Dewi; Christyana Sandra; Eri Witcahyo (Universitas Airlangga, 2019)
Background: A clinical pathway is a concept of an integrated service which describes the stages of healthcare services from the admission until the return of  patients based on the medical service standards and evidence-based nursing care with measurable results. Kaliwates General Hospital is an accredited hospital with a clinical pathway. Typhoid case was the highest disease in 2017 at Kaliwates General Hospital. Aims: This study aims to describe the resources at Kaliwates General Hospital in the implementation of clinical pathways, especially typhoid fever treatment. Method: This study was a descriptive and qualitative study. Nine respondents were selected using purposive sampling, including one internist and the quality team at Kaliwates General Hospital. The variables studied include human resource factors, budget factors, method factors, and time factors. Results: The results suggested that the human resources at Kaliwates General Hospital had high commitment, motivation, and moderate knowledge in the implementation of clinical pathways. All equipment and documents were considered adequate. The communication among the implementers was good, but compliance and training for staffs were considered less prominent. The task division of each staff was fairly distributed even though the pharmacy unit perceived that the division was quite unfair. Conclusion: The implementation of the clinical pathway for typhoid fever treatment at Kaliwates General Hospital runs quite well. The hospital must identify and plan staff training regularly, prepare the job description appropriately, and perform performance appraisal based on the job description that has been developed. Keywords: clinical pathway, typhoid fever, resource.